1, 4-Dihydropyridyl complexes of magnesium: synthesis by pyridine insertion into the magnesium–silicon bond of triphenylsilyls and catalytic pyridine hydrofunctionalization. Issue 36 (31st May 2018) - Lemmerz, L. E.; Spaniol, T. P.; Okuda, J.
Abstract : Magnesium triphenylsilyl complexes [Mg(SiPh3 )2 (THF)2 ] and [(Me3 TACD)Mg(SiPh3 )] ((Me3 TACD)H = 1, 4, 7-trimethyl-1, 4, 7, 10-tetraazacyclododecane) serve as precursors for 1, 4-dihydropyridyl complexes of magnesium which are active in the hydroboration of pyridine. Abstract : Magnesium bis(triphenylsilyl) [Mg(SiPh3 )2 (THF)2 ]·THF (1 ) reacted with a stoichiometric amount of pyridine to give the magnesium 4-(triphenylsilyl)dihydropyridyl complex [Mg(NC5 H5 -4-SiPh3 )2 (THF)3 ] (2 ). Using an excess of pyridine, a mixture of magnesium dihydropyridyl [Mg(NC5 H6 )2 (py)4 ] (3 ) and 4-(triphenylsilyl)pyridine was formed. Complex3 underwent exchange with pyridine- d 5 at 25 °C to give [Mg(NC5 D5 H-4)2 (py- d 5 )4 ] (3-HD ). Analogous reactions with Me3 TACD-supported magnesium triphenylsilyls [(Me3 TACD)Mg(SiPh3 )] (4 ) and [(Me3 TACD·AlEt3 )Mg(SiPh3 )] (6 ) ((Me3 TACD)H = Me3 [12]aneN4 : 1, 4, 7-trimethyl-1, 4, 7, 10-tetraazacyclododecane) with pyridine gave [(Me3 TACD)Mg(NC5 H5 -4-SiPh3 )] (5 ), [(Me3 TACD·AlEt3 )Mg(NC5 H5 -4-SiPh3 )] (7 ) and a mixture of [(Me3 TACD)Mg(NC5 H6 )] (8 ) and 4-(triphenylsilyl)pyridine. Complex8 is also formed by reacting3 with (Me3 TACD)H and underwent exchange with pyridine- d 5 at higher temperatures. The activation energy for the exchange is about 25 kJ mol −1 higher than that for the exchange reaction of3 to3-HD . Complexes2, 3, 3-HD, 5, 7 and8 were characterized by NMR spectroscopy and3, 5 and8 by single crystal structure analysis. Complex3 was found to be slightly active in the hydrosilylation of pyridine using phenylsilane, whereas complex8 showed no activity. Both complexes3 and8 were active in the hydroboration of pyridine with pinacolborane.